Experimental methods in entrepreneurship research: the status quo. Issue 6 (5th September 2016) - Kraus, Sascha; Meier, Fabian; Niemand, Thomas
Abstract : Purpose: The purpose of this paper is to evaluate the emerging field of experimental research on entrepreneurship to better understand its development and potential. Design/methodology/approach: A systematic, evidence-based literature review was applied, resulting in a sample of 47 articles having used experiments in entrepreneurship research so far. The papers are analyzed according to their topic, methods, and research design, revealing insight into their limitations and prospective contributions. Findings: The paper discusses the potential and disadvantages of experimental methods while arguing for experiments as the method of choice for answering causality questions. This study finds a persistent increase in experimental entrepreneurship research since its introduction in 1990. Research limitations/implications: The study provides research from the field of entrepreneurship with future directions, with potential research areas and an orientation for those interested in conducting experiments. Originality/value: Experiments are employed in a variety of research areas and have become more and more popular in the field of entrepreneurship. No study has analyzed the experimental studies in entrepreneurship. This paper contributes by providing an overview of the field, reflecting and discussing the outcomes while characterizing the methods employed.